PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) PADA LAPORAN KEUANGAN KSU GAHARU ENDE - Ai, Stefania Nofembi; Londa, Yulita (Jurnal Riset Ilmu Akuntansi, 2022)
SAK ETAP is a financial accounting standard that is used as a guideline in the preparation of reports for entities that do not have public accountability such as MSMEs and cooperatives. This study aims to find out whether KSU Gaharu Ende has applied the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP) to its financial statements. The type of research in this study is qualitative research. The data collection method from this study was obtained from observations, interviews, documentation studies as well as literature studies. Based on the results of the research conducted, the results were obtained that KSU Gaharu has applied the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in the preparation of its report. However, this application has not fully occurred because the financial statements made by KSU Gaharu are only in the form of balance sheets, income statements (remaining results of business), statements of changes in equity, statements of cash flows without making notes on the statements. In addition, in the financial statements of KSU Gaharu, the presentation of current assets has not been based on the order of liquidity and the purchase of equipment is recorded as costs.